Good Language Learner and Motivation - Faravani, Akram; Majid Mohammed, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the interrelationships between learner motivation and good language learning. The study participants were 30 students studying English at Hafez language institute in Mashhad. The students’ motivation was measured through BALLI questionnaire. Their language ability in English was identified based on their GPA of the last 3 terms. Then the learners were divided into two groups of good language learners and bad language learners based on their GPA. To analyze the data the researcher used a Chi square and compared the responses of the good language learners (over achievers) to that of bad language learners (under achievers). The results of the study revealed the existence of positive and significant relationships among the two variables.